Speech‐in‐noise perception is a marker of preclinical Alzheimer's disease. (31st December 2021) - Waters, Sheena; Watson, Cameron; Jacobs, Benjamin M.; Foote, Isabelle F.; Dey, Sumit; Noyce, Alastair J.; Marshall, Charles R.
Abstract: Background: Central auditory function is affected early in the course of Alzheimer's disease, and may be useful as a prodromal disease marker. Speech‐in‐noise perception is a simple test of central auditory function. Method: We used Speech Reception Threshold (SRT) as a measure of speech‐in‐noise perception in 160, 905 healthy subjects in UK Biobank. We assessed odds ratios for incident Alzheimer's disease by SRT quintile at a mean follow up of 10 years. In a subgroup of 37, 082 healthy subjects with contemporaneous cognitive testing and brain imaging we assessed the relationships of SRT with cognitive performance and structural neuroanatomy using voxel‐based morphometry (VBM). Result: Poorer (higher) SRT was associated with greater odds of incident Alzheimer's disease (odds ratio for quintile 5 relative to quintile 1: 2.91 (95%CI 1.92‐4.57); p=0.000001). Worse SRT was associated with poorer cognitive performance in multiple domains. VBM revealed symmetrical grey matter correlates of SRT in a distributed network of auditory and speech perception areas, as well as medial temporal lobe structures. Conclusion: Speech‐in‐noise perception is a simple non‐invasive assay of cognition, brain structure and risk of incident Alzheimer's disease, and as such may be readily translatable as a cost‐effective tool for dementia risk stratification at large‐scale.